Identification of promising wheat lines resistant to tan spot (Pyrenophora tritici-repentis) - Raimbekova, B.; Anuarova, L.; Kyrbasova, E.; Imanova, E.; Sartayeva, A.; Doszhanova, A. (Fundamental and Experimental Biology, 2026)
Wheat tan spot (yellow spot) is one of the most widespread and dangerous fungal diseases of wheat, caused by the phytopathogenic fungus Pyrenophora tritici-repentis. The aim of the study is to identify resistance to tan spot in promising wheat lines based on phenotypic indicators and molecular screening. A comprehensive assessment of wheat samples was carried out by the biomass index (NDVI), resistance to pathogens (PTR, AUDPC) and molecular markers. It was found that NDVI varies from 65 to 82, while high values (> 75) correlate with resistance (R² = 0.652), and low values (<70) — with susceptibility (S). Resistant samples (12 pcs., PTR = 5–10), including the Salamouni variety, and susceptible ones (7 samples, PTR = 15–35) were identified. As a result of molecular screening, PCR analysis of all studied genotypes showed the presence of the recessive gene tsn1 in 11 wheat genotypes (64.7 %). The integral indicator AUDPC (mean=70.8) demonstrated high variability (CV>50 %) and extreme values (up to 165). Statistical analysis confirmed the stability of NDVI (CV=6.5–6.7 %) and significant variability of PTR/AUDPC, reflecting mixed resistance. The results emphasize the need for an in-depth study of the relationship of molecular markers with resistance to tan spot.